Uncovering communication strategies used in language‐discordant consultations with people who are migrants: Qualitative interviews with healthcare providers - Brittany M. C. Chan; Jeanine Suurmond; Julia C. M. vanWeert; Barbara C. Schouten (Wiley, 2024)
Abstract Background Global migration has led to a sharp increase in the number of language‐discordant consultations (LDCs) in healthcare. Evidence on how healthcare providers (HCPs) meet migrant patients' needs while mitigating language barriers is lacking. Design Using purposive and snowball sampling, we recruited twenty‐seven Dutch HCPs (Mage = 45.07, SD = 11.46) and conducted semi‐structured interviews to collect qualitative, open‐ended data for identifying the communication strategies used with migrant patients in LDCs. We analysed the transcripts using deductive and inductive approaches (e.g., constant comparative method from Grounded Theory). Final pattern codes (i.e., key themes) were discussed among the research team until mutual agreement had been achieved. Results Five key themes emerged from the analyses: HCPs often 'got‐by' with (1) instrumental and (2) affective communication strategies used in language‐concordant consultations to start medical consultations. When some instrumental communication strategies were deemed ineffective (e.g., lingua franca, gesturing, etc.) to bridge language barriers, HCPs turned to (3) incorporating digital tools (e.g., Google Translate). When HCPs were unable to communicate with migrant patients at all, (4) informal, ad‐hoc and professional interpreters were involved. Finally, HCPs often (5) involved additional support to engage migrant patients to engage in treatment‐related behaviours. Discussion and Conclusions Our results highlight the importance of raising awareness among HCPs about using various combinations of different strategies. The development of a guideline indicating the optimal combination of communication strategies for different medical consultation goals may be useful in reshaping the current communication behaviour of HCPs in LDCs. Patient or Public Contribution HCPs were the study population involved in this qualitative study. Refugee health advisors, general practitioners and linguistic specialists (i.e., members of the Right2Health consortium) with experience with the Dutch healthcare system were involved throughout the development of this research. This includes a review of the research question, participant information sheet and interview topic guide as well as providing interpretations of the data and feedback to this manuscript.